2018
DOI: 10.31940/logic.v18i3.1127
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Implementation of Occupational Health and Safety Management System on Workers Productivity on Structural Finishing Works of Reinforced Concrete Columns

Abstract: The implementation of the project from year to year is significantly improved on implementation aspects of cost, quality, and time, in order to manage the use of human resources to be realistic. Occupational health and safety in a company is often ignored especially for companies which are doing project developments. This also affects the occupational safety of the workers and occupational illness arisen after the projects have been implemented. So in running safe business, occupational health and safety manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Based on a literature review, several studies have reported similar findings that achievement motivation significantly influences employee productivity (Budiwati & Shinuranti, 2019;Laksmiari, 2019;Purwaningsih et al, 2021). Research on the effectiveness of occupational safety and health management on employee productivity has been reported by (Has & Susanty, 2016;Santiana et al, 2018), with findings indicating that the effectiveness of occupational safety and health management significantly affects employee productivity. Recent research on work productivity has been reported by (Jaafar & Rahim, 2022), who investigated the mediating effects of job autonomy and work-family conflict on the relationship between telecommuting and employee productivity, and by (Kurdy et al, 2023), who studied the mediating effects of job level on the relationship between remote work and employee productivity.…”
mentioning
confidence: 99%
“…Based on a literature review, several studies have reported similar findings that achievement motivation significantly influences employee productivity (Budiwati & Shinuranti, 2019;Laksmiari, 2019;Purwaningsih et al, 2021). Research on the effectiveness of occupational safety and health management on employee productivity has been reported by (Has & Susanty, 2016;Santiana et al, 2018), with findings indicating that the effectiveness of occupational safety and health management significantly affects employee productivity. Recent research on work productivity has been reported by (Jaafar & Rahim, 2022), who investigated the mediating effects of job autonomy and work-family conflict on the relationship between telecommuting and employee productivity, and by (Kurdy et al, 2023), who studied the mediating effects of job level on the relationship between remote work and employee productivity.…”
mentioning
confidence: 99%